Inventarisasi Kearifan Lokal Ghatib Beghanyut Masyarakat Siak Sri Indrapura - A S Retno Ningsih; Yunus Winoto; Elnovani Lusiana (Universitas Galuh, 2023)
The tradition of rejecting reinforcements for the Siak community and an intangible cultural heritage that needs to be preserved by taking an inventory. This research aims to discover local wisdom regarding the Ghatib Beghanyut tradition in Siak Sri Indrapura. This study uses a qualitative method with a descriptive. The technique of collecting data in this research is by conducting interviews, observing, and conducting literature studies. The results of this study indicate that: 1) Historically, this tradition has existed since the XII Sultan of Siak; 2) Conceptually, this tradition is a regeneration activity through knowledge transfer, the actualization of religious values, ongoing activities, and their implementation of every Safar month between the 7th, 8th, 9th or 22nd, 23rd, 24th. This is adjusted to the low tide of the river. 3) The Ghalib Beghanyut tradition has undergone several location changes and has additional agendas, such as grave pilgrimages. This research concludes that cultural inventory is significant to be carried out as a form of cultural preservation and can make young people aware of the importance of maintaining and using existing culture in the future.